Effects of Solvent Composition on Profile of Total Extracts, Phenolic Compounds, and Antifungal Activity of Sterculia quadrifida R.Br Bark - Rollando Rollando (Journal of Global Pharma Technology, 2019)
Faloak bark extract has antibacterial, antioxidant and anticancer potential but no optimal solvent has found to extract the active compounds of faloak bark. Therefore, it is necessary to optimize the solvent against the faloak bark. This study aims to determine the optimum solvent of methanol, ethyl acetate, petroleum ether, and water in order to produce an optimal response value in the extract, total phenolic, and inhibitory results in antifungal tests. Extracts obtained through reflux extraction for 2 hours and extract yield calculated. The extract results tested to determine the total phenolic content and inhibition of antifungal test. The determination of the optimum solvent composition carried out using Rstudio v.3.2.2 software with ANOVA parametric test or Kruskal-Wallis non-parametric test and using Design Expert v.11 software with Simplex Lattice Design (SLD) method. The results showed that the solvent composition of faloak bark extract (Sterculia quadrifida R.Br) in giving the yield of extract, total phenolic, and optimal antifungal inhibition was methanol:water 0,438:0,562.